Proceedings of the second international Conference of the international Society for Terrain-Vehicle systems : August 29-September 2, 1966, Quebec City, Quebec, St. Jovite, Quebec, Hamilton, Ontario, Canada - Siddall, James N.; Southwell, P. H. (Peter Henry), 1924- (University of Toronto Press, 2018)
This volume combines papers presented at the Second International Conference on the International Society for Terrain-Vehicle Systems.